Urynkowione znaki pamięci : Kultura historyczna w warunkach kultury (post)konsumpcyjnej (Politeja, 2020)
Commodified Memory Emblems. Historical Culture in the (Post)Consumptional CulturePostmodernist consumption, developed by the order of self-realisation, increasingly shapes current historical awareness. Consequently, contemporary collective memory is composed not of dates and historical facts but of visual identification, slogans and varied communicative practices, so the components of popular brands which stimulate people’s consumable attitudes. The symbols of the Polish Resistance Movement during World War II as well as national colours and emblem move from historical and commemorative sphere to the sphere of pop culture. They commonly appear on T-shirts, tattoos, murals, social media profiles and political banners and are used to clarify the present day through the prism of the past, to articulate people’s ideas, concerns and affinities. The ‘language’ of memory boom surprisingly corresponds to the rhetoric of present global cultural industry, which is the ‘natural environment’ of communication for Millennials and Post-Millennials. The article is an attempt to summarise the most influential academic perspectives of current memory culture, dominated by media and consumable practices.